2014
DOI: 10.3163/1536-5050.102.3.005
|View full text |Cite
|
Sign up to set email alerts
|

A survey study of evidence-based medicine training in US and Canadian medical schools

Abstract: Findings can provide a starting point for discussion to develop a standardized competency framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 8 publications
(19 reference statements)
3
76
1
1
Order By: Relevance
“…35 To the authors' knowledge, this is the first study to specifically examine MLE curricula in US schools of pharmacy. The described curricula were similar in scope to curricula of evidence-based medicine in medical schools in the United States, Canada, and the United Kingdom, 36,37 although medical schools may include more formal education in the practice setting than pharmacy education. 38,39 A formal analysis of student MLE activities during APPEs should be conducted to allow measurement of evidencebased practice, 40 an important educational outcome.…”
Section: Discussionmentioning
confidence: 89%
“…35 To the authors' knowledge, this is the first study to specifically examine MLE curricula in US schools of pharmacy. The described curricula were similar in scope to curricula of evidence-based medicine in medical schools in the United States, Canada, and the United Kingdom, 36,37 although medical schools may include more formal education in the practice setting than pharmacy education. 38,39 A formal analysis of student MLE activities during APPEs should be conducted to allow measurement of evidencebased practice, 40 an important educational outcome.…”
Section: Discussionmentioning
confidence: 89%
“…In a larger survey by Blanco et al (2014), the authors found that librarians were not sharing innovative approaches. This study would have benefited from investigating whether participants are effective at communicating EBM teaching strategies.…”
Section: Commentarymentioning
confidence: 99%
“…Blanco, Capello, and Dorsch (2014) and Maggio et al (2016) have also reported on librarians' roles in EBM design, implementation, and assessment. The strength of this study is that it identifies librarians' perceptions of their own training needs.…”
Section: Commentarymentioning
confidence: 99%
“…Health sciences librarians train health professions students and trainees in EBP question formulation, searching, and some critical appraisal skills [50][51][52].…”
Section: The New Challengementioning
confidence: 99%